Identifying the photon absorption characteristics of Cr-doped Cu2ZnSnS4 (CZTS:Cr) thin film deposited by Co-sputtering technique - Sapeli M.M.I.; Chelvanathan P.; Hossain M.I.; Sajedur Rahman K.; Yusoff Y.; Amin N. (Elsevier B.V., 2024)
This study investigates the potential of a quaternary compound semiconductor to be realized as the absorber layer for third-generation intermediate band solar cells (IBSCs). In this work, the effects of Cr doping into Cu2ZnSnS4 (CZTS) host material to form intermediate band within the forbidden bandgap were studied. The films were deposited by a co-sputtering technique. It has been found that Cr has a high preference to substitute Zn, followed by Sn, then Cu. Insufficient Cr does not lead to intermediate band but, instead, forms defect states within the bandgap. Excess Cr however deteriorates CZTS (112) peak while at the same time secondary phase of cubic-ZnCr2S4 starts to grow. At sufficient levels of Cr content, absorption coefficient tremendously improved to 105 cm?1, resulting in an additional absorption peak attributed to possible formation of an intermediate band. This intermediate band is located at 1.40 0.02 eV below CBM, while the band gap Eg is 1.55 eV. Further optimization to the sulphurization process reveals that the intermediate band peak, ECIL could be adjusted towards blue or red shift by manipulating Cr and/or sulphur content. This yields a bandgap of 1.52 eV with two intermediate bands positioned at 0.90 eV and 1.20 eV above the VBM. These preliminary findings are beneficial prior to realizing a working device of CZTS:Cr intermediate band solar cell. 2023 Elsevier B.V.